The History and Development of the Persatuan Tarbiyah Islamiyah (PERTI) - Lulu Syafi Zakiyah; Zahra Nur Alfiyah; Sitatun Akhiroh (Tarikhuna: Journal of History and History Education, 2024)
The Minangkabau language and traditions, with strong geographical and cultural Islamic identity, are dominantly adhered by the Ahlusunnah Waljama’ah and Madzhab Syafi’i. Establishing Suraus as educational institutions, marked as the beginning of Islamization. Most of education system in Minangkabau was based on surau since it was first emerged from the region. Persatuan Tarbiyah Islamiyah establishment was caused by transformation from traditional surau-centered Islamic education to a more sophisticated system. The formation of this organization was also influenced by the struggle of Syaikh Sulaiman Arrasuli after his return from Mecca. This research aims to provide deeper insights regarding history and the development of Persatuan Tarbiyah Islamiyah. A literature review was conducted using several steps: selecting relevant literature, tracing sources, reading the literature, and taking the step of reading the sources thoroughly to gain new insights and form a theoretical framework. The findings of this research indicate that the split in PERTI in 1944 was caused by a shift in the organization's focus, from social-community activities to a more politically oriented direction, as well as a shift of the organization's center from Bukittinggi to Jakarta.